Bibliometric analysis of acute pancreatitis in Web of Science database based on CiteSpace software - Sun, Wenjie; Huang, Pinxian; Song, Hualing; Feng, Dianxu (Medicine (Baltimore), 2020)
Recent years have witnessed some controversial viewpoints in clinical and basic research, which exert a great influence on the research trend of acute pancreatitis (AP). We aimed to analyze the literature on AP by metrology, co-occurrence, co-citation, and visualization, and to explore the research status and trend in this field in the past 5 years. The relevant literature collected in Web of Science Core Collection (WoSCC) database from 2015 to 2019 was searched using "acute pancreatitis" as the title word, and the co-occurrence analysis of authors, institutions, countries, and keywords was carried out by using CiteSpace V. On this basis, the keywords were clustered and analyzed by using VOSviewer 1.6.8 and Carrot 2 software, and a visual map was drawn. A total of 2035 articles were included, with an average annual volume of more than 400. The high-yield authors were mainly Chinese, among which Li WQ was the most prominent. Most of these articles were from universities and institutions of high-yielding countries including China, the United States, and India. The main sources of journals were professional journals, among which Pancreas and Pancreatology have the most literature collection volume (both over 100), including clinical and basic research. Among the funds, the National Natural Science Foundation of China and NIH were the main 2 sponsors. Disciplinary attributes involved multiple subjects such as gastroenterology, internal medicine, and surgery. Keyword co-occurrence and clustering results showed that the classification, mortality, and risk factors of AP were still more concerned, and the research trend of this disease was the molecular mechanism of the severity of AP. CiteSpace can be used to analyze the knowledge graph of AP, to show its development status initially and intuitively, and to provide a reference for topic content and its further development.